Determination of the prevalence of mental illnesses in 2 rural areas of Kerman - S.H MOtamedi; M.T Yasemi; H Karbasi; GH Bani vaheb (Journal of Kerman University of Medical Sciences, 1997)
Based on the WHO reports,1% of world population suffer from a sever psychological disorders,and 5-15% suffer from a mild disorder.based on the present informations in Iran,1-6 percent of the people above 15 years of age suffer from a severe psychological disorder and 15.2% suffer from the mild form of the disease.to investigate the epidemiology of mental illnesses in two rural areas of Baft,(Gugher and khabre) and denerate baseline data for future comparisons (after integration of mental health into primary health care),SCL -90-R questionaire was filled for 1086 inhabitants.all the permanent inhabitants (excluding nomads)over 15 years of age were given symptoms checklist 90 revised (SCL-90-R) which has been standardized for Iranian population.Drop-out nrate was not  significant(2 men and 3 women).the point prevalence of mental disorders was 41.1%.the prevalence of mild,moderate,and severe disorders were 31.3% ,8% and 0.3% respectively.somatic  problems were the most prevalent(54.3%) and phobia the least(18.5%).all the scales were higher in women than in men,and similar studies in Iran.however,some studies using other questionaires other than SCL-90R have reported similar results.based on the findings of this study itis recommended to provide mental health services for rural population especially high risk groups such as women.